Correlation between Physical Activity with Sexual Libido of Male Office Workers in Grogol Subdistrict, Sukoharjo - Lauraine Wijayaningtyas Sinuraya; Rosalia Sri Hidayati; Bhisma Murti (Nexus Kedokteran Komunitas, 2014)
Backgrounds: Sexual libido or sexual desire has been referred to as desire, appetite, drive and the motivation to seek out sexual satisfaction. Reduced libido is widely considered the symptomatic reflection of low testosterone levels in man. Physical activity is one way to increase testosterone release into circulation from Leydig cell in testis that can affect the libido itself. Objection of this research is to find whether a physical activity related to sexual libido, especially in Grogol Subdistrict, Sukoharjo. Methods: This research was an observational analytic research in cross sectional approaching that had been done at Grogol Subdistrict, Sukoharjo on Mei-June 2014. The study is conducted on 40 samples according to the inclusion and exclusion criteria that have been set. Data were collected from questionnaires by respondents. The data were statistically tested with Chi Square test, which is followed by using Multiple Logistic Regression Analysis to determine the relationship between variables which has controlled the confounding variable. Results: The statistical analysis result for Multiple Logistic Regression Analysis shows the value of p = 0.816 and Odds Ratio = 1.23. Conclusions: Based on the test result of Multiple Logistic Regression Analysis, it can be concluded that physical activity and sexual libido of male office workers in Grogol Subdistrict, Sukoharjo, is related in a negative way, but the result was not statistically significant. Keywords: Sexual libido, physical activity, stress, male office worker.